Nitrate in drinking water and risk of birth defects: Findings from a cohort study of over one million births in Denmark - Leslie Thomas Stayner; Anja Søndergaard Jensen; Jörg Schullehner; Vanessa R. Coffman; Betina B. Trabjerg; Jørn Olsen; Birgitte Hansen; Marie Pedersen; Carsten B. Pedersen; Torben Sigsgaard (Elsevier, 2022)
Summary: Background: A few studies have reported an increased risk of birth defects (BD) with maternal exposure to nitrate in drinking water. We examined this association in a large cohort study with well-characterized exposure. Methods: Danish singletons liveborn to Danish-born parents from 1991-2013 were identified using civil and patient registries (n=1,018,914). Exposure to nitrate was estimated using a spatial model based on national data linked with individual addresses. Odds ratios (OR) and 95% confidence intervals (95% CI) were estimated using logistic regression. Findings: In total, 33,182 cases of BD were identified. Nitrate concentrations were generally well below US and EU standards. We observed an exposure-response relationship (p=0·004) between nitrate during pregnancy and eye BD, and increased risk in the highest exposure group (≥25 mg/L nitrate) (OR: 1·29; 95% CI: 1·00, 1·66). An interaction was observed between maternal age and continuous nitrate exposure for nervous system BD (p<0·001) indicating an increased risk among mothers <25 years-of-age (OR for 10 mg/L (OR10): 1·20; 95% CI: 1·06, 1·35). An interaction (p<0.01) with maternal age and continuous nitrate exposure was also observed for ear, face, and neck BD indicating an increased risk among babies born to mothers <25 years-of-age (OR10: 1·35; 95% CI: 1·11, 1·66). There was evidence of an inverse exposure-response relationship for any, digestive system, female genital, and urinary BD. Interpretation: Our study is the first to report an association between nitrate and eye BD and BD of the ear, face, and neck. It also provides support to prior reports of increased risk of nervous system BD. Funding: This study was supported by a grant from the United States National Institute of Environmental Health Sciences (R01 ES027823-01A1).